Role of Arabs (Tribes of Bani Hilal) In Morocco in the era of the Al-Moahideen - Emaraga Elabbar, Nanat; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2017)
This Study Aims to Shed Light on One of The Components of Society in Morocco In the Era of The Al Moahideen, Namely the Arabs (Tribes of Bani Hilal). The New Study Will Include Their Ratios, Their Original Place of Origin and How They Migrated to The Maghreb Until I Spoke About Their Relationship with The State of The Al Moahideen, Which Was Characterized by Hostility at The Beginning Until Some of The Successors of The Al Moahideen Succeeded Sometimes by Tenderness, And Sometimes by Force. Their Homes and Their Centres of Influence by Engaging Them in Their Wars Against the Christians Of Andalusia And to Get Rid of The Strife and Unrest That They Were Having. Hence The Importance Of The Study In Shedding Light On The Role Played By The Arabs In The State Of The Al Moahideen In The Far Morocco, Which Will Be Clear In The Face Of The Power Of The State By Their Contribution To The Victory In Several Battles, And Also Shows The Weakness Of The State And The Decline By Exploiting Those Conditions For Their Benefit, And Their Gains Increased Of The Poor State, And That They Were Not A Direct Cause Of Their Weakness And Fall.